Mechanical failure mode causes of in-wheel motors - Biček, Matej (Strojniški vestnik, 2015)
The presented survey includes a comprehensive overview of mechanical failure mode causes for direct driven electric in-wheel motors. As electric vehicles evolve and develop, in-wheel motor driven vehicles gain acknowledgement, more and more papers are published in order to show individual design challenges and overcoming solutions for failure causes and effects. Obtainable literature is mainly concerned with integral electrical failure modes, neglecting structural causes and effects which in some cases interact. The presented paper inspects the most likely potential mechanical causes of failure modes for in-wheel motors and shows related paper%s results for comparison and reference. As several mechanical and electromagnetic layouts and construction topologies exist, only the most promising and generally used one has been studied within this work in order to emphasize sensible directions of further development. Failure mode and effects analysis (FMEA) has been made with severity rating which present mechanical failure potential for permanent magnet synchronous motors intended for in-wheel motor application.
Keywords: analiza potencialnih okvar in njihovih učinkov; ekscentričnost; kolesni elektromotorji; odpoved ležaja; povečana nevzmetena masa; povečane vibracije